2009
DOI: 10.1590/s0103-65642009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da memória de trabalho em crianças com transtorno do déficit de atenção e hiperatividade

Abstract: Introduction: Attention deficit hyperactivity disorder (ADHD) compromises cognitive abilities. Executive functioning is one of the most affected dimensions, particularly working memory. We aimed to assess the impact of ADHD specifically on working memory. Methods: Using selected sub-tests of the Portuguese version of Psycholinguistic Assessments of Language Processing in Aphasia (PALPA), we compared the performance of 37 children with ADHD to 67 children from the control group. Results: Children with ADHD show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
2
6
0
2
Order By: Relevance
“…The G2 individuals showed greater who have ADHD, both in the analysis of the variable "age" and the variable "comorbidity", which is consistent with the literature, as it found no statistical significance in the working memory processes of individuals with ADHD 7,26 . It was also necessary to compare working memory performance according to the presence or absence of age-related comorbid conditions (Table 3).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The G2 individuals showed greater who have ADHD, both in the analysis of the variable "age" and the variable "comorbidity", which is consistent with the literature, as it found no statistical significance in the working memory processes of individuals with ADHD 7,26 . It was also necessary to compare working memory performance according to the presence or absence of age-related comorbid conditions (Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…However, the ability to rapidly retrieve stored information through the executive functions is impaired in individuals with ADHD, since these abilities demand cognitive processes supraordinated by organized behaviors that depend directly on self-regulation and inhibitory behavior 3,25 . Authors 26 concluded that children with ADHD have similar cognitive abilities to those who do not have the disorder; however, because of the attentional difficulties, children afflicted with ADHD take longer to acquire the necessary skills for academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Quando realizada a comparação entre os escolares do GI e do GII, observa-se diferença estatisticamente significante apenas nas provas de leitura de palavras não frequentes (LPNF) e leitura de não palavras (LNP) do processo léxico, corroborando a literatura que afirma que a habilidade de codificação, alteração em consciência fonológica, limitação da memória e na formação de léxico prejudicam o desenvolvimento das habilidades necessárias para a leitura 23,24,[38][39][40] , características em comum encontradas na dislexia e no TDAH.…”
Section: Discussionunclassified
“…Results affirm Messina and Tiedemann (2009), Sowerby, Seal & Tripp (2011) and Bolden et al studies (2012, who reported that children with ADHD have greater inattention and this would probably be one of the causes of low capacity in MT. In studies Schweitzer et al (2000), Andrade (2002), Oliveira (2007) and Rapport et al (2008), individuals with ADHD also showed lower performance than expected, also affirming the results found in this study.…”
Section: Discussionmentioning
confidence: 58%